Conceptual Model for Assessment in STEM Subjects in Higher Education - Barragán Moreno, Sandra; Guzmán Rincón, Alfredo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Learning outcomes have been incorporated into multiple assessment systems to evaluate the level of student academic achievement. In this context, the objective of this article was defined as conceptually modeling the assessment of student academic achievement in STEM subjects at the higher education level focused on learning outcomes. For this purpose, the methodology employed included four consecutive phases that allowed the development of a conceptual model that integrates the dimensions of assessment, the requirements of learning outcomes, and disciplinary aspects. A future opportunity is the successive application, in different institutions, for a holistic reflection including the students' appreciation.